The Role of the Center For Dialogue And Cooperation Among Civilizations (Cdcc) In Order To Strengthen Space Free Public - Amir Fiqi (Trigin Publisher, 2022)
After the fall of the authoritarian New Order and the formation of a new era, namely the era of reformation, a free public space is open to the public by providing a place for the public to express their freedom and autonomy in the form of freedom of the press, freedom of parties, freedom of common sense, freedom of belief, freedom of expression. sense, freedom to defend oneself, freedom to defend community, regional autonomy, independence, and freedom to gather for discussion and dialogue. In this thesis, the author tries to explain how the role of the Center for Dialogue and Cooperation among Civilizations (CDCC) is in the context of strengthening free public spaces, especially in the dialogue segment. In this thesis the author uses a qualitative method with a descriptive approach by observing the data obtained in the field. In this script, The writer uses participatory observation, interviews and documents as data collection techniques. The role played by the CDCC is to facilitate a free and independent public space for citizens with different religious or cultural backgrounds to speak, discuss and dialogue to discuss religious issues and even state issues in order to criticize and control the government in order to form good governance. Even though they take the elite segment, they are not elitist because the meetings (dialogues) held by the CDCC always discuss issues related to the interests of the lower classes who are always excluded from the policies produced by the government. The CDCC is also concerned with dialogues related to religion and belief by always holding meetings between followers of different religions in order to create a pluralist and tolerant society. As a form of implementing the role of the CDCC in an effort to establish a free public space in the life of society and the state, the CDCC conducts a dialogue or discussion. The forms of dialogue or discussion conducted by the CDCC are inter-religious dialogue, dialogue about politics, cultural dialogue and dialogue related to the economy.